Gαi3-Dependent Inhibition of JNK Activity on Intracellular Membranes - Bastin, Guillaume; Yang, Jin Ye; Heximer, Scott P. (Frontiers in Bioengineering and Biotechnology, 2015)
Heterotrimeric G-protein signaling has been shown to modulate a wide variety of intracellular signaling pathways, including the mitogen-activated protein kinase (MAPK) family. The activity of one MAPK family class, c-Jun N-terminal kinases (JNKs), has been traditionally linked to the activation of G-protein coupled receptors (GPCRs) at the plasma membrane. Using a unique set of G-protein signaling tools developed in our laboratory, we show that subcellular domain-specific JNK activity is inhibited by the activation of Gαi3, the Gαi isoform found predominantly within intracellular membranes, such as the endoplasmic reticulum (ER)–Golgi interface, and their associated vesicle pools. Regulators of intracellular Gαi3, including activator of G-protein signaling 3 (AGS3) and the regulator of G-protein signaling protein 4 (RGS4), have a marked impact on the regulation of JNK activity. Together, these data support the existence of unique intracellular signaling complexes that control JNK activity deep within the cell. This work highlights some of the cellular pathways that are regulated by these intracellular complexes and identifies potential strategies for their regulation in mammalian cells.